'Circling the Circumference of Silence': Ghosts and Modernism in Postwar Kawabata Yasunari. Issue 1 (2nd January 2019) - Nihei, Masato; Solomon, Joshua Lee
ABSTRACT: Kawabata Yasunari (1899–1972) held a deep interest in modern spiritualism and applied his knowledge of it to his literary process in diverse ways. Spiritualism was widely employed as metaphor and narrative methodology in twentieth-century literary modernism, and Kawabata stood out among his peers for his prolific use of it. It has typically been assumed that Kawabata distanced himself from modernism after World War II, enacting a complete return to 'Japanese tradition'. Yet modernist and spiritualist connections can still be observed in his writing during that period. This paper looks at the connections between postwar Kawabata and contemporary modernism, focusing in particular on a close reading of the short story 'Mugon' [Silence] (1953). The story is framed by an episode involving a haunted tunnel and depicts a series of events as a novelist visits an elderly writer who has fallen mute due to illness. Kawabata uses stream-of-consciousness narration to present radical ideas about literary composition and the relationship between language and reality and subverts common-wisdom understandings of language and literature. I conclude that the composition of 'Mugon' demonstrates clear continuity between Kawabata's pre- and postwar writings.